Discordant cfDNA‐NIPT result unraveling a trisomy 12 chronic lymphocytic leukemia in a 37 years old pregnant woman. (7th May 2022) - Di Giosaffatte, Niccolò; Bottillo, Irene; Laino, Luigi; Iaquinta, Giovanni; Ferraris, Alessandro; Garzia, Mariagrazia; Bargiacchi, Simone; Mulargia, Claudia; Angelitti, Maria Rosaria; Palumbo, Fabiana; Grammatico, Barbara; Bartolelli, Cinzia; et al.
Key points: What's already known about this topic? Discordant NIPT results can rarely unravel maternal malignancies, especially when multiple chromosomal imbalances are reported. Both solid and hematological neoplasms have been described. What does this study add? This is the first case of a discordant NIPT result due to Chronic Lymphocytic Leukemia associated with trisomy of the chromosome 12. Putative maternal malignancy should be considered and investigated through sensitive techniques even in presence of a single chromosomal anomaly. This must be considered especially when the imbalance is known to recur in hematological neoplasms.